Students' motivation toward science learning in secondary schools in Oman and Malaysia: A comparative study - Salih, Maria; Mai, Mohammed Y.M.; Al Shibli, Abdullah (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The purpose of this research was to compare the Omani and Malaysian students' motivation toward science learning in secondary schools. Motivation is an important component from any teaching and learning process. The results of previous studies revealed that students with better motivation usually perform better in school grades. The sample size is 359 students: 37.6% of them were Malaysian (135 students) while 62.4% were Omani (224 students). The 30-item Science Motivation Questionnaire (SMQ) was used in this research. It was developed by Glynn, Taasoobshirazi and Brickman. The results showed that the students had a “moderate” motivation in general. Regarding the subcategories, the students had “high Extrinsically Motivation” while they had a “moderate” level of motivation in the other subcategories or motivational factors. An independent-samples t-test was conducted to compare the motivation towards science scores of Omani and Malaysians. This finding implied that the Omani students were more motivated to science learning than the Malaysian students. On the other hand, the result showed that there was a significant difference between male and female whereas the females were highly motivated to science learning in general, but both of them had the same level of self-efficacy.